Evaluating the Effectiveness of SEAMOLEC's Online Training Using the Kirkpatrick’s Model - Rumita Sihole; Beatriks Lasamahu; Esther Ida Krisanti; Arie Susanty; Zahrani Balqis (Southeast Asian Journal on Open and Distance Learning, 2025)
Training evaluation stands as a critical phase in the training process, dedicated to investigating and providing feedback for the conducted training over a certain period. This research aims to conduct online training evaluation level 3 and 4 using Kirkpatrick analysis framework for continuous improvement.      The research investigates the effectiveness of SEAMOLEC's online training program using a comprehensive mixed-methods approach both quantitative and qualitative methodologies. The research findings aim to offer a thorough understanding of the training's impact on participants' behavior (level 3) and organizational results (level 4). The research utilizes questionnaires and interviews with alumni and the head of the organization as instruments. The analysis of the effectiveness of SEAMOLEC's online training programs revealed positive outcomes at both the individual and organizational levels. At the behavior level (level 3), parameters such as support (3.74), application of acquired knowledge (3.63), productivity improvement (3.68), relevance of the training (3.67), and knowledge-sharing practices (3.52) demonstrate favorable results. For organizational results (level 4), participants exhibit significant skill improvement (3.71), commendable job-related assistance (3.57), substantial collaboration success (3.71), and goal achievement (3.57). Through this holistic evaluation, the research seeks to offer valuable insights and recommendations for enhancing the quality and outcomes of SEAMOLEC's online training initiatives.